Ethnic differences in the degree of morning blood pressure surge and in its determinants between Japanese and European hypertensive subjects: data from the ARTEMIS study - Hoshide, Satoshi; Kario, Kazuomi; de la Sierra, Alejandro; Bilo, Grzegorz; Schillaci, Giuseppe; Banegas, José Ramón; Gorostidi, Manuel; Segura, Julian; Lombardi, Carolina; Omboni, Stefano; Ruilope, Luis; Mancia, Giuseppe; et al. (Hypertension (Dallas, Tex. 1979), 2015)
Morning blood pressure (BP) surge has been reported to be a prognostic factor for cardiovascular events. Its determinants are still poorly defined, however. In particular, it is not clear whether ethnic differences play a role in determining morning surge (MS) size. Aim of our study was to explore whether differences exist in the size of MS between Japanese and Western European hypertensive patients. We included 2887 untreated hypertensive patients (age 62.3±8.8 years) from a European ambulatory BP monitoring database and 811 hypertensive patients from a Japanese database (Jichi Medical School Ambulatory Blood Pressure Monitoring WAVE1, age 72.3±9.8 years) following the same inclusion criteria. Their 24-hour ambulatory BP monitoring recordings were analyzed focusing on MS. Sleep-trough MS was defined as the difference between mean systolic BP during the 2 hours after awakening and mean systolic BP during the 1-hour night period that included the lowest sleep BP level. The sleep-trough MS was higher in Japanese than in European hypertensive patients after adjusting for age and 24-hour mean BP levels (40.1 [95% confidence interval 39.0-41.2] versus 23.0 [22.4-23.5] mm Hg; P<0.001). This difference remained significant after accounting for differences in night-time BP dipping. Age was independently associated with MS in the Japanese database, but not in the European subjects. Our results for the first time show the occurrence of substantial ethnic differences in the degree of MS. These findings may help in understanding the role of ethnic factors in cardiovascular risk assessment and in identifying possible ethnicity-related differences in the most effective measures to be implemented for prevention of BP-related cardiovascular events.